Loss of retinal cadherin facilitates mammary tumor progression and metastasis - Agiostratidou, Georgia (2009)
The mammary epithelium is thought to be stabilized by cellcell adhesion mediated mainly by E-cadherin (E-cad). Here, we show that another cadherin, retinal cadherin (R-cad), is critical for maintenance of the epithelial phenotype. R-cad is expressed in nontransformed mammary epithelium but absent from tumorigenic cell lines. In vivo, R-cad was prominently expressed in the epithelium of both ducts and lobules. In human breast cancer, R-cad was down-regulated with tumor progression, with high expression in ductal carcinoma in situ and reduced expression in invasive duct carcinomas. By comparison, E-cad expression persisted in invasive breast tumors and cell lines where R-cad was lost. Consistent with these findings, R-cad knockdown in normal mammary epithelium stimulated invasiveness and disrupted formation of acini despite continued E-cad expression. Conversely, R-cad overexpression in aggressive cell lines induced glandular morphogenesis and inhibited invasiveness, tumor formation, and lung colonization. R-cad also suppressed the matrix metalloproteinase 1 (MMP1), MMP2, and cyclooxygenase 2 gene expression associated with pulmonary metastasis. The data suggest that R-cad is an adhesion molecule of the mammary epithelium, which acts as a critical regulator of the normal phenotype. As a result, R-cad loss contributes to epithelial suppression and metastatic progression. ©2009 American Association for Cancer Research.